CaV6O16·2.8H2O with Ca2+ Pillar and Water Lubrication as a High‐Rate and Long‐Life Cathode Material for Ca‐Ion Batteries. (30th March 2022) - Wang, Junjun; Wang, Jianxiang; Jiang, Yalong; Xiong, Fangyu; Tan, Shuangshuang; Qiao, Fan; Chen, Jinghui; An, Qinyou; Mai, Liqiang
Abstract: Due to the low cost and low redox potential of calcium, calcium ion batteries (CIBs) are considered a competitive candidate for large‐scale energy storage systems and have attracted increasing attention in recent years. However, the development of CIBs is still in its infancy and hindered by the lack of high‐performance cathode materials. Herein, the metahewettite layered vanadium oxide with the Ca 2+ pillar and water lubrication is reported as a cathode material for CIBs. Benefiting from the large interlayer spacing, pillar, and water lubrication effect, the as‐prepared CaV6 O16 ·2.8H2 O (CVO) delivers a high discharge capacity of 175.2 mAh g −1 at 50 °C and 131.7 mAh g −1 at room temperature, a long cycle life of 1000 cycles and the highest rate performance (up to 1000 mA g −1 ) in organic electrolyte. Furthermore, a single‐phase Ca 2+ insertion and extraction reaction is revealed by in situ X‐ray diffraction and in‐situ Fourier transform infrared spectroscopy. Density functional theory computations indicate that Ca 2+ tends to diffuse along the b direction with a low energy barrier of 0.36 eV in CVO. This work is bringing the performance of cathode materials for CIBs to a higher level and of great significance for accelerating the development of CIBs. Abstract : CaV6 O16 ·2.8H2 O as cathode materials for calcium ion batteries delivers a high discharge capacity of 175.2 mAh g −1, a long cycle life of 1000 cycles, and the highest rate performance. A single‐phase Ca 2+ insertion and extraction reaction is revealed by in situ X‐ray diffraction and in situ Fourier transform infrared spectroscopy. Density functional theory computations indicate that Ca 2+ tends to diffuse along the b direction in CaV6 O16 ·2.8H2 O.